Synthesis and biological evaluation of novel tyrosyl-DNA phosphodiesterase 1 inhibitors with a benzopentathiepine moiety. Issue 9 (1st May 2015) - Zakharenko, Alexandra; Khomenko, Tatyana; Zhukova, Svetlana; Koval, Olga; Zakharova, Olga; Anarbaev, Rashid; Lebedeva, Natalya; Korchagina, Dina; Komarova, Nina; Vasiliev, Vladimir; Reynisson, Jóhannes; Volcho, Konstantin; et al.
Graphical abstract: Abstract: Tyrosyl-DNA phosphodiesterase 1 (TDP1) is a promising target for antitumor therapy based on Top1 poison-mediated DNA damage. Several novel benzopentathiepines were synthesized and tested as inhibitors of TDP1 using a new oligonucleotide-based fluorescence assay. The benzopentathiepines have IC50 values in the range of 0.2–6.0 μM. According to the molecular modeling, the conformational flexibility of the dibutylamine group of the most effective inhibitor (3d ) allows it to occupy an advantageous position for effective binding compared to its cyclic counterparts. The study of cytotoxicity of these compounds revealed that all compounds cause an apoptotic cell death in MCF-7 and Hep G2 cells. Therefore the new class of very effective inhibitors of TDP1 was elaborated.